Leukocyte–mimicking Pluronic–lipid nanovesicle hybrids inhibit the growth and metastasis of breast cancer. Issue 12 (8th March 2019) - Chen, Qinyue; Chen, Yiting; Sun, Yali; He, Wenxiu; Han, Xiaoli; Lu, Enhao; Sha, Xianyi
Abstract : We have constructed a novel biomimetic Pluronic-lipid nanovesicle hybrid that mimics leukocytes, to target breast cancer and suppress metastasis. Abstract : Breast cancer is a severe threat to the health of women, and the metastasis of tumor cells leads to high mortality in female patients. Evidence shows that leukocytes are recruited by breast tumors through adhesion to inflammatory endothelial cells as well as tumor cells. Moreover, it is known that Pluronic P123 is effective in the reduction of matrix metalloproteinases (MMPs), which play a key role in the degradation of the extracellular matrix (ECM), therefore helping tumor cells to escape from the primary site. Inspired by these mechanisms, we established a leukocyte–mimicking Pluronic–lipid nanovesicle hybrid (LPL) through integrating the membrane proteins extracted from leukocytes with membrane-like vesicles, with Pluronic P123 hybridized in the lipid bilayer, while paclitaxel (PTX) was selected as the model drug. The hybrid vesicles were perfectly incorporated with the leukocyte membrane proteins, and no disruption to the lipid membrane was caused by P123, with the bio-targeting ability of leukocytes and the MMP-9-downregulation effect of P123 fully preserved in LPL. LPL exhibited enhanced cellular uptake and anti-metastasis efficacy in in vitro assays, while significant tumor targeting capabilities were also found through biodistribution assays. Moreover, the in vivo therapeutic effects of PTX-loaded LPL (PTX-LPL) were observed, with an 80.84% inhibition rate of tumor growth and a 10.62% metastatic rate of tumor foci in lung tissue. Furthermore, the amounts of MMP-9 and neutrophils in the tumor as well as in the lung were greatly reduced with PTX-LPL. In summary, LPL may have potential applications in metastatic breast cancer therapy.